Strengthening Women’s Roles Through Banking Support for Sustianable Maritime Sector Development - Lasty Agustuty; St. Ramlah; Aulia Damayanti; Patimah Patimah (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to analyze the factors influencing business credit disbursement by banks and their impact on increasing the capacity of MSMEs and sustainable economic growth. The sample in this study was women entrepreneurs in the coastal tourist area of Bulukumba Regency. The analytical method used was a mixed-method approach, with quantitative measures using path analysis and qualitative measures using a hermeneutic approach. The results indicate that the credit security system banks offer is an essential factor in entrepreneurs' credit decision-making. Furthermore, the results also demonstrate the influence of bank credit disbursement on increasing the capacity of MSMEs, both in terms of income and capability. This increase in business capacity can ultimately impact the country's economic growth